O eterno espanto: uma leitura estética em Mario Quintana - Barata Junior, Carlos Roberto Rodrigues (2010)
This work aims to read the phenomenon of the Sublime as the main aesthetical concern in the work of the Brazilian poet Mario Quintana. The research was based on the dialogical approach used by Mario Quintana to see life & poetry. This search noticed that such aesthetical concern is an answer to the modern age that surrounds the post-war man. Immerse in his aesthetical concerns, Mario Quintana designs, through his poetry, a way to give humanity back to men. In this attempt of rupture, Mario Quintana returns to tradition through astonishment besides laughter